Behcet's disease: reproductive function and pregnancy - Z. S. Alekberova; D. A. Bizhanova (Современная ревматология, 2018)
The problem of fertility and pregnancy outcomes in rheumatic diseases (RDs) is discussed by both rheumatologists and obstetricians. The present paper considers the problems of reproductive function and pregnancy outcomes in patients with Behcet's disease (BD).The study of the circulating level of anti-MЯllerian hormone (AMH) opened a new page in the evaluation of ovarian function and fertility in different diseases, including RDs. The evaluation of AMH as a marker of ovarian reserve substantially simplified its estimate and the determination of the contribution of the disease itself to patients' infertility.Examination of the obstetric histories of patients with BD demonstrated different pregnancy outcomes. Our studies of familial aggregation in BD showed that there were large families in certain ethnic groups, which allowed us to evaluate, on the basis of obstetric histories, both reproductive function and pregnancy outcomes, and not one pregnancy, but several pregnancies, which is important in the study of fertility.Data on the impact of pregnancy on BD, and vice versa, are scarce and contradictory; described as both an exacerbation of BD during gestation and improvement of disease symptoms. There is evidence for an exacerbation of BD in the third trimester of pregnancy only in the women who had painful genital ulcers. At the same time, a number of works have not reveal the impact of either BD on the outcome of gestation or that of pregnancy on the course of BD.It is concluded that there is a need for further investigations of fertility, pregnancy and its outcomes in BD.